Investigation of dynamical structure of solar radio burst type iii and the tendencies to form type ii burst based on coronal mass ejections events (CMES) in low frequency radio region / Zety Sharizat Binti Hamidi - Hamidi, Zety Sharizat (2014)
Coronal Mass Ejections (CMEs) are well known as one of the most massive eruptions which potentially create major disturbances in the interplanetary medium and initiate severe magnetic storms when they collide with the Earth‟s magnetosphere. As indicated with radio signatures so-called type II and III burst it also divided by sub-type of burst depending on the physical characteristics and different mechanisms. For empirical case studies, the statistical properties of both solar bursts by using the Compound Astronomical Low-cost Low-frequency Instrument for Spectroscopy in Transportable Observatories (CALLISTO) network data has been analyzed. The aim of the present study is to reveal dynamical properties of solar burst type II and III due to several mechanisms. Such mechanisms are based on statistical properties of type II and III burst itself, physical parameters and other factors that might affect the dynamical and instabilities of the explosion of the Sun activities. From the analysis (2006 2011) data, it is found that the tendencies of type III bursts form a type II burst is only 9.0579%. The statistical data also shown that out of 16 events, 13 events on the evolution of SRBT II are formed after a group of SRBT III and intermittently. It can be construed that almost 61.5% solar radio burst type III is dominant in the range of 300 MHz till 499 MHz. This represents a distribution of 1.2407 x 10-6 eV to 2.0637 x 10-6 eV. Most of the cases of both solar radio bursts can be found in the range less that 400 MHz. Based on solar flare monitoring within 24 hours, the CMEs that has the potential to explode will dominantly be a class of M1 solar flare. Overall, the tendencies of SRBT III burst form the SRBT II burst at 187 MHz to 449 MHz. In conclusion, this range is a current regime of solar radio bursts during CMEs events.